PERILAKU SOSIAL PESERTA DIDIK YANG MENGIKUTI PEMBINAAN EKSTRAKULIKULER PENCAK SILAT - TAUJIRI, YUSUP (2014)
This research was motivated by the rise of juvenile delinquency and social behavior unethical by most learners, on the other hand are active learners in extracurricular activities pencak silat training showed positive social behaviors. This study aims to identify trends in the social behavior of students who followed the extracurricular coaching, as well as showing a more concrete empirical evidence about the benefits of participating in extracurricular activities pencak silat training relating to social behavior of learners. The method used is the method of ex post facto causal comparative research design. This research was conducted in SMP N 2 Gebang Cirebon. The samples used were taken purposively sampling criteria pesrta students who have followed the extracurricular coaching pencak silat over the years as many as 30 people and learners who do not follow the extracurricular coaching as many as 30 people. Instrument of social behavior of students using a questionnaire. In this study data was analyzed by oriented hypothesis testing through test T-test. The results of the research students who follow the guidance extracurricular activities have higher social behaviors than students who did not attend extracurricular activities. Social behavior is the most dominant role behavior, then the behavior of expressive and behavioral social relationships. T-tests of the test obtained P-Value (sig.) 0,000 where the value is smaller than 0.050 so the hypothesis is rejected. In the end it can be concluded that the social behavior of students who followed the extracurricular coaching pencak silat tend to be better than the social behavior of students who did not follow the coaching extracurricular activities. Keywords: social behavior, extracurricular, pencak silat, SMP N 2 Gebang ABSTRAK YUSUP TAUJIRI : Prilaku Sosial Peserta Didik Yang Mengikuti Pembinaan Ekstra Kulikuler Pencak Silat Penelitian ini dilatar belakangi oleh maraknya kenakalan remaja dan prilaku sosial yang kurang pantas oleh sebagian besar peserta didik, di sisi lain peserta didik yang aktif di kegiatan pembinaan ekstrakulikuler pencak silat menunjukan perilaku sosial yang positif. Penelitian ini bertujuan untuk mengetahui kecenderungan perilaku sosial peserta didik yang mengikuti pembinaan ekstrakulikuler, serta menunjukkan bukti empirik yang lebih konkrit tentang keuntungan berpartisipasi dalam kegiatan pembinaan ekstrakulikuler pencak silat yang berkaitan dengan prilaku sosial peserta didik. Metode penelitian yang digunakan adalah metode ex post facto dengan desain penelitian causal comparative. Penelitian ini dilaksanakan di SMP N 2 Gebang Kabupaten Cirebon. Sampel yang digunakan diambil secara purposif sampling dengan kriteria pesrta didik yang sudah mengikuti pembinaan ekstrakulikuler pencak silat lebih dari satu tahun sebanyak 30 orang dan peserta didik yang tidak mengikuti pembinaan ekstrakurikuler sebanyak 30 orang. Instrumen perilaku sosial peserta didik menggunakan angket. Pada penelitian ini analisis data dilakukan dengan berorientasi kepada pengujian hipotesis melalui uji T-Tes. Hasil penelitian peserta didik yang mengikuti kegiatan pembinaan ekstrakulikuler memiliki perilaku sosial yang lebih tinggi dibanding peserta didik yang tidak mengikuti kegiatan ekstrakulikuler. Perilaku sosial yang paling dominan adalah perilaku peran, selanjutnya perilaku ekspresif dan perilaku hubungan sosial. Dari uji T-Tes didapat P-Value (sig.) 0,000 dimana nilainya lebih kecil dari 0,050 sehingga hipotesis ditolak. Pada akhirnya dapat ditarik kesimpulan bahwa perilaku sosial peserta didik yang mengikuti pembinaan ekstrakulikuler pencak silat cenderung lebih baik dibandingkan dengan perilaku sosial peserta didik yang tidak mengikuti kegiatan pembinaan ekstrakulikuler.